2010
DOI: 10.1128/jvi.00077-10
|View full text |Cite
|
Sign up to set email alerts
|

Wide Variation in the Multiplicity of HIV-1 Infection among Injection Drug Users

Abstract: Recent studies indicate that sexual transmission of human immunodeficiency virus type 1 (HIV-1) generally results from productive infection by only one virus, a finding attributable to the mucosal barrier. Surprisingly, a recent study of injection drug users (IDUs) from St. Petersburg, Russia, also found most subjects to be acutely infected by a single virus. Here, we show by single-genome amplification and sequencing in a different IDU cohort that 60% of IDU subjects were infected by more than one virus, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
186
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 183 publications
(201 citation statements)
references
References 48 publications
10
186
5
Order By: Relevance
“…Here, our more detailed sampling clearly shows that primary HIV-1 specific T cell responses can select recombination between distinct T/F viruses even more rapidly, within weeks of infection when pVL is stabilizing prior to the establishment of setpoint. These observations provide empirical evidence of a mechanism beyond stochastic events to explain the emergence of recombination reported in acute infection [12,14,15,17]. A striking feature of the results presented here are the five independent recombinations observed in a very short time period and the fact that two separate T cell responses, neither immunodominant, combined to select the recombinations.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Here, our more detailed sampling clearly shows that primary HIV-1 specific T cell responses can select recombination between distinct T/F viruses even more rapidly, within weeks of infection when pVL is stabilizing prior to the establishment of setpoint. These observations provide empirical evidence of a mechanism beyond stochastic events to explain the emergence of recombination reported in acute infection [12,14,15,17]. A striking feature of the results presented here are the five independent recombinations observed in a very short time period and the fact that two separate T cell responses, neither immunodominant, combined to select the recombinations.…”
Section: Discussionsupporting
confidence: 49%
“…The proportion of multiple T/F viruses initiating infection increases in other groups, such as men who have sex with men and intravenous drug users. Infection with multiple T/F viruses is linked to factors that are known to increase overall transmission rates, such as higher risk sex acts and other concurrent sexually transmitted infections [12,[15][16][17][18][19]. Several studies have associated infection with multiple HIV-1 T/F viruses, multiple subtypes, and/or a diverse virus population, with higher pVL setpoint, faster CD4+ T cell decline, earlier need for anti-retroviral therapy and a worse prognosis for the infected individual [14,[20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, by sequencing plasma virion RNA (vRNA) in the first few weeks following transmission, it is possible to enumerate and infer the genome(s) of the virus(es) that established the infection (9,(12)(13)(14). In the absence of adaptive immune pressures, HIV-1 diversifies in a random fashion, with viral sequences exhibiting a Poisson distribution of mutations and a star-like phylogeny that coalesces to an inferred consensus sequence.…”
mentioning
confidence: 99%
“…This consensus sequence represents the genome of the virus that initiated the infection, termed the transmitted founder (TF) virus (9). Single genome amplification (SGA) of plasma vRNA, which precludes PCR artifacts such as Taq polymerase-mediated recombination (15)(16)(17)(18), revealed that in the great majority (∼80%) of sexual transmission cases, a single TF virus establishes the new infection (9,12,13,(19)(20)(21).…”
mentioning
confidence: 99%